EVOLUTION OF LATIN GRAMMAR: A COMPREHENSIVE ANALYSIS OF ORIGINS AND HISTORICAL DEVELOPMENT - Kenjayeva , Nigora (Универсальная индексная библиотека Евразийского журнала социальных наук, философии и культуры, 2024)
This comprehensive article explores the evolution of Latin grammar, tracing its origins from Proto-Indo-European to the refined structures of Classical Latin, and its subsequent transformations into Vulgar and Medieval Latin. The author meticulously examines the historical development of Latin grammar, highlighting the influences of linguistic contact, social dynamics, and literary traditions on its evolution. Through comparative analysis and linguistic theory, the article sheds light on the analytical methods employed by scholars to reconstruct the grammar of Proto-Indo-European and trace its continuity through various stages of Latin. Textual evidence, including inscriptions, manuscripts, and grammatical treatises, is cited to illustrate the formalization and standardization of Latin grammar during the Classical period, as well as its adaptation and assimilation into diverse linguistic contexts during the medieval era. Overall, the article provides a comprehensive understanding of Latin grammar's origins, historical development, and analytical frameworks, reaffirming its significance as a cornerstone of linguistic scholarship and cultural heritage.